Education in the area of heart and vessel diseases for 40+ citizens - Olišarová, Věra; Tóthová, Valérie; Šedová, Lenka; Bártlová, Sylva; Chloubová, Iva; Michálková, Helena; Prokešová, Radka; Trešlová, Marie (Česká kardiologická společnost, 2018)
Introduction and goal: The heart and vessel diseases rank among main causes of death worldwide. In the Czech Republic, they account for a high proportion of hospitalizations. Although such diseases can be very well influenced through elimination of influenceable risk factors, their prevalence in the Czech population is still high. That leads to rising need to increase the efficiency of health education activities. Therefore the article aims at revealing the current status of education in the area of prevention of cardiovascular diseases, as seen by the citizens themselves, thus providing a feedback that can help to improve the situation in this area. Methods: The current status of education in the area of cardiovascular diseases, as seen by the citizens, was investigated through a combination of a non-standardized questionnaire with the SF-36 standardized questionnaire. The investigation took place all over the Czech Republic during April 1–20, 2016. The statistical data analysis was made under use of the SASD program, version 1.4.12. The selection set of citizens consisted of 1992 respondents; from the perspective of age segmentation of the basic set, the data are representative for individual groups of Czech citizens aged 40 years and more. Results and conclusion: It was found out that 71.5% Czech citizens aged 40 years and more were educated in the physician's office on the ways to improve their health condition. 71.4% citizens described the physician as the education carrier, while 25.4% respondents assigned that role to the nurse. Within the area of influenceable risk factors, 50.8% respondents were educated in the area of nutrition, 51.0% were educated in the area of blood pressure home measurement, and 52.9% in the area of exercise. 43.9% respondents were educated on the issue of smoking, and 36.0% respondents on the issue of excessive abuse of alcohol. It was also shown that respondents who can be considered endangered for different reasons were educated in greater amount. That seems insufficient from long-term perspective, with regard to the demographic trends and the concept of active ageing, particularly because of the fact that the role of education consists not only in the effort to contribute to improve the quality of life but also in delaying the manifestation of diseases and of the economic risks related to the decreasing number of economically active persons.
Edukace v oblasti onemocnění srdce a cév u občanů 40+
Keywords: Cardiovascular diseases; Physician; Nurse; Education; Risk factors; kardiovaskulární choroby; lékař; sestra; edukace; rizikové faktory